Penyuluhan Perawatan Kesehatan Gigi dan Mulut Pada Remaja - Erni Susanty Tahir; Puput Mulyono (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2025)
The lack of knowledge, attitudes, and actions among children regarding dental and oral health care is due to the lack of health education. One way to improve this is through education using videos and mentoring. Most adolescents in Gentan Village have dental and oral health problems, with the target of dental and oral health in adolescents only reaching 70%, indicating relatively low dental and oral health levels. This service aims to provide education through audiovisual media and mentoring to adolescents about dental and oral health care, increase knowledge, and provide an understanding of the parts of the teeth, as well as how to properly brush teeth, including brushing the front, sides, chewing surfaces, deep parts, and tongue. This community service is carried out by providing health education using audiovisual media and mentoring. Through this activity, it is hoped that adolescents will become more aware of the importance of maintaining dental and oral hygiene and can properly perform the correct brushing technique to prevent dental caries and toothaches. At the end of the service, there was an increase in understanding and a change in attitudes from negative to positive in preventing dental caries. The results of this activity showed an increase in knowledge and a positive attitude toward dental and oral care. Therefore, this education and mentoring are important to increase children's awareness of the importance of brushing their teeth for better health.